Feasibility Analysis Of Rice Business Local Farmers In Kampung Urumb, Semangga District, Merauke Regency, South Papua Province - Ineke Nursih Widyantari; Retnowati Wiranto; Prihadi Beni Waluyo; Arum Ambarsari; Gerzon Jokomen Maulany; Stanley HD Loppies (Journal of Global Sustainable Agriculture, 2025)
Urumb is local villages located in Semangga District with the acreage of 18.000 KM2. It has rice fields with the potential area about 750 ha and in harvest season of 2017, the local farmers have been able to maximize approximately 555 ha land for rice planting. This study was conducted to recognize the profit margin, profitability value and the effiency of rice farming of local farmers in Urumb Village, District of Semangga, Regency of Merauke. This experiment used analysis of farming income, Profitability as well as Return and Cost Ratio. Primary data were collected from question sheet and interogation; while secondary data were provided by Statistics of Indonesia.The results showed that rice farming in Urumb Village, District of Semangga, Regency of Merauke, Province of Papua was beneficial, with the gain profit of IDR 6,731,452/ha, the profitability of 0.65, and income analysis (R/C) about 1.65.